Cultural Guidelines for Commercial Production of Boston fern (Nephrolepis exaltata ‘Bostoniensis’) - William Schall; Heqiang Huo; Jianjun Chen (EDIS, 2018)
‘Bostoniensis’, or Boston fern, is a popular sword fern variety that is one of the most important foliage crops in the ornamental plant industry. This 5-page article describes common Boston fern cultivars, provides guidelines for their culture and interior use, and lists physiological problems that may be encountered during production and interiorscape use. Written by Bill Schall, Heqiang Huo, and Jianjun Chen and published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep550